'Brand-Centred Control': A Study of Internal Branding and Normative Control. Issue 7 (July 2017) - Müller, Monika
In this article I present brand-centred control as a new form of normative control and examine the ways in which it affects employees. To do so, I draw on the results of a qualitative case study of a consumer products company with a strong corporate culture and brand, and examine internal branding as an extension of culture management. The key insights of the case study show that brand-centred control – unlike traditional normative control that typically works inside the company – also engages an external audience (customers, fans, and the wider public) as an additional source of normative control. As employees internalise the brand image of this external audience, they turn into brand representatives even in absence of face-to-face interactions with others and in their private lives. Brand-centred control thus blurs the boundaries between work and employees' private lives in unprecedented ways. I discuss the ways in which employees respond to and resist brand-centred control and point to further research on brand-centred control as a significant new form of normative control.